Quality of Youth‐Friendly Service and Associated Factors at the Public Health Facilities of Awi Zone, Northwest Ethiopia: A Mixed Study - Gashaw Alamineh; Alemtsehay Mekonnen Munae; Melash Belachew Asiresie; Mekonen Melkie Bizuneh; Zemenu Shiferaw Yadita (Health Science Reports)
ABSTRACT Background and Aims Adolescents and young adults necessitate access to quality health services that cater to their needs as they transition into adulthood. However, research from both the developed and developing nations reveals services tailored to this demographic are often vary greatly in quality. Moreover, there′s a dearth of data on the standard of youth‐friendly health services in our research area. Therefore, this study assessed the quality of youth‐friendly service, and associated factors in the public health facilities of the Awi Zone, Northwest Ethiopia. Method A mixed study (cross‐sectional and phenomenological‐qualitative) was conducted between March 14 and April 19, 2023, involving 619 adolescents across 10 health facilities. A systematic random sampling was employed. Data were collected using a semi‐structured questionnaire and a standard checklist. Assessment of youth‐friendly health services quality utilized the Donabedian framework. Data were entered into Epi‐data version 3.4 and analyzed using SPSS version 25. Binary logistic regression analysis was used to identify associated factors. Qualitative data underwent thematic analysis. Result None of the health facilities met the ≥ 75% across all quality components. The process‐related quality showed the most significant shortcomings. Factors associated with client satisfaction (output‐related quality) included: age (15–19) (AOR = 0.68, 95% CI: 0.48, 0.96), shorter time to reach the facility (≤ 30 min) (AOR = 1.60, 95% CI: 1.06, 2.42), nonpayment for services (AOR = 1.49, 95% CI: 1.008, 2.22), and shorter waiting times (≤ 30 min) (AOR = 2.33, 95% CI: 1.41, 3.84). Financial constraints, staff turnover, long wait times, payment requirements, and high client loads emerged as barriers in qualitative findings. Conclusions Adolescent and youth‐friendly health services fell below WHO′s quality standards. Structure‐related quality affected by insufficient trained staff, unavailability of guidelines/protocols, and lack of adolescent involvement in facility governance. Process quality suffered from providers′ non‐compliance with national guidelines. Improvements need training in client handling, involving youth in governance, and ensuring provider adherence to guidelines.